Platinum RTD sensor based multi-channel high-precision temperature measurement system for temperature range −100°C to +100°C using single quartic function. Issue 1 (1st January 2018) - Sarkar, Shantanu
Abstract: A method and system for measuring multiple temperature points using two wire configuration Resistance Temperature Detectors (RTD) for temperature range − 100°C to +100°C is mainly composed of the Micro Controller Unit (MCU), analog–digital converter (ADC), reference Voltage source, Multiplexers (MUX) and resistance network including the RTD temperature sensors. The RTDs are sequentially scanned using a reference/constant voltage source, and resistance values of the RTDs are calculated based on the voltage measured across the RTDs and the current sensing resistor. Improving the precision of temperature measurement is based on a line fitting algorithm—Newton's divided differences interpolation polynomial based on three reference resistor values representing two extreme end points and the center point of the temperature range for which the system is made. The test results show that the device temperature measurement precision can reach ±0.02°C, has the advantage of using a single quartic function for the entire temperature range − 100°C to +100°C with dynamic calibration to address errors related to in-circuit resistance, tolerance, temperature coefficient, linearity and offset errors in the circuit, and also supports detection of degradation of linearity and offset in the circuit because of the aging factor.